2016
DOI: 10.2139/ssrn.2831718
|View full text |Cite
|
Sign up to set email alerts
|

Esports Corruption: Gambling, Doping, and Global Governance

Abstract: The world of esports is fast becoming a mainstream form of competition and entertainment. While there is debate over whether esports should be recognized as a sport, the emergence of competitive video gaming has seen a rise in many of the problems associated with traditional sport including: doping, gambling-related match-fixing and non-gambling related corruption. Indeed, the esports gambling market has quickly surpassed the total legal sports wagering market in the United States, including daily fantasy spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 4 publications
0
39
0
3
Order By: Relevance
“…But, esports are not local competitions held at shopping malls, as video game tournaments once were. They are now commercial pursuits with sponsorships for top performers, sold‐out stadiums for live‐viewing, venture capital‐like investments and a tethered wagering market expected to reach US$23.5 billion by the year 2020 . Indeed, the world‐wide esports audience (participants and viewers) is anticipated to be upwards of 435 million people by 2019 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…But, esports are not local competitions held at shopping malls, as video game tournaments once were. They are now commercial pursuits with sponsorships for top performers, sold‐out stadiums for live‐viewing, venture capital‐like investments and a tethered wagering market expected to reach US$23.5 billion by the year 2020 . Indeed, the world‐wide esports audience (participants and viewers) is anticipated to be upwards of 435 million people by 2019 .…”
mentioning
confidence: 99%
“…A 2017 article from ESPN reported that amongst five popular esports titles the average age of professionals was between 21.2 and 25.5 . Beyond roots in South Korea, esports teams are now emerging on a growing number of collegiate campuses, with some schools handing out scholarships to prized recruits in the same way that they have courted football or basketball phenoms in the past . Although often discussed in the singular, esports more accurately describe a variety of different competitive video game titles in a manner like the Olympics is a conglomeration of many different sports.…”
mentioning
confidence: 99%
See 3 more Smart Citations